TO THE PROBLEM OF TECHNICAL AND TECHNOLOGICAL FACTORS OF E-LEARNING EFFICIENCY - Kovalchuk, Halyna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article highlights the features of modern factors of e-learning effectiveness in the conditions of distance learning. The structure and efficiency criteria, factors and components of e-learning quality assessment are presented. The main goal-oriented approach to the development of ICT in distance education is indicated. The following segments of e-Learning quality are described. It was concluded that it is necessary to provide all possible and relevant forms of teacher support, consistent with the requirements for the quality of e-learning, which students consider important, to ensure the online mode, taking into account the teacher’s right to time, qualifications and providing appropriate and desired technical means of communication according to the requirements to the technical quality of communicative and cooperative online learning processes.